CFD aplicado ao escoamento rotacional laminar e isotérmico para fluidos de Bingham em região anular - Silvestre, Marcos Vinícios (2013)
Fluid mechanics is a fundamental science in engineering, as it provides the principles and techniques needed to design fluid dynamic systems and devices that work effectively, safely and efficiently in a wide range of applications. It plays a critical role in modern engineering, contributing to technological progress and the development of innovative solutions. The aim of this work was to study the laminar flow of Bingham fluids in an annular region, where the inner wall is rotating and the outer wall is stationary, and to observe the behavior of these fluids with different critical shear stresses and different apparent viscosities. Thus, the behavior of the fluids was analyzed by means of computational fluid dynamics (CFD) simulations using the GAMBIT and Ansys Fluent Student software to create the geometry, mesh and perform the simulations, which allowed a comparison between the tangential velocity profiles along the annular region with the algebraic solution obtained through the Transport Equations. The results obtained both via CFD and analytical solution were close, with an average deviation of no more than 2.63% for the tangential velocity, considering these two approaches. In short, it was noted that fluids with the same Bingham number behave in a similar way in relation to viscous flow when subjected to shear forces, thus presenting the same velocity profile. Thus, the higher the critical shear stress, the greater the fluid's resistance to flow, where the increase in the critical shear stress of the Bingham fluid becomes more pronounced as it moves away from the inner wall, due to the dissipation of force that occurs until it reaches the outer wall, where the tangential velocity tends to zero. Finally, the study revealed favorable results in the simulation of the case, showing remarkable agreement when compared to the algebraic solutions.